CARBON CAPTURE AND STORAGE (CCS) POTENTIAL AT LOW-RESISTIVITY RESERVOIR USING PETROPHYSICAL ANALYSIS AT "SOKA JINGGA" FIELD, TALANG AKAR FORMATION, ASRI BASIN - Yusriyah, Dzakiyah; Syafri, Ildrem; Mohamad, Febriwan; Ralanarko, Dwandari; Aprillia, Belinda Rizka (Journal of Geological Sciences and Applied Geology, 2024)
Carbon Capture and Storage (CCS) is a new technology that uses subsurface reservoirs to reduce carbon dioxide emissions by storing it below the surface. PT XYX conducted a comprehensive exploration of the CCS potential in Indonesia. The “Soka Jingga” Field, located at Talang Akar Formation, Asri Basin, is a potential candidate for CCS. The “Soka Jingga” Field has low resistivity reservoirs. There are five wells at “Soka Jingga” Field, namely DZ-1, DZ-2, DZ-3, DZ-4, and DZ-5. The objective of this study is to assess the CCS potential in the laminated sand interval of the “Soka Jingga” Field. The research method used is petrophysical analysis. The petrophysical data processing results show porosity values ranging from 23% to 35.5% with a net reservoir thickness ranging from 5.25 ft to 65 ft. The highest capacity was found in DZ-4 in the Zelda Member Zone 3, amounting to 37,923,654,924.52 kg or 37,923,654.92 tonnes. Summing the total capacity at "Soka Jingga" Field, the total CO2 storage capacity in the research area is 125,169,497,575.91 kg or 125,169,497.58 tonnes.